2011
DOI: 10.1016/j.ajpath.2011.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Amyloidogenicity and Clinical Phenotype Associated with Five Novel Mutations in Apolipoprotein A-I

Abstract: The phenotype of hereditary apolipoprotein A-I amyloidosis is heterogeneous with some patients developing extensive visceral amyloid deposits and end-stage renal failure as young adults and others having only laryngeal and/or skin amyloid, which may be of little clinical consequence. Clinical management and prognosis of patients with systemic amyloidosis depend entirely on correct identification of the fibril protein, such that light chain amyloidosis (AL, previously referred to as "primary"), the most frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 39 publications
(40 reference statements)
2
91
0
4
Order By: Relevance
“…3 More than 50 natural variants of ApoA-I have been described, and a little over one third are associated with familial amyloidosis, with 19 known mutations in the APOA1 gene. 2,[4][5][6][7][8][9] Eriksson et al have described different patterns of organ involvement by hereditary ApoA-1 amyloidosis based on specific mutations in hot-spot regions of the APOA1 gene: Mutations in coding regions 50-93 were more likely to cause hepatic and renal involvement, whereas mutations in regions 173-178 were more prone to cardiac, laryngeal, and cutaneous involvement. 10 In addition, the peptide comprising residues 46-59 forms amyloidlike fibrils, and researchers have suggested that this region is responsible for selfrecognition, aggregation, and overall amylogenic propensity of ApoA-1 amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…3 More than 50 natural variants of ApoA-I have been described, and a little over one third are associated with familial amyloidosis, with 19 known mutations in the APOA1 gene. 2,[4][5][6][7][8][9] Eriksson et al have described different patterns of organ involvement by hereditary ApoA-1 amyloidosis based on specific mutations in hot-spot regions of the APOA1 gene: Mutations in coding regions 50-93 were more likely to cause hepatic and renal involvement, whereas mutations in regions 173-178 were more prone to cardiac, laryngeal, and cutaneous involvement. 10 In addition, the peptide comprising residues 46-59 forms amyloidlike fibrils, and researchers have suggested that this region is responsible for selfrecognition, aggregation, and overall amylogenic propensity of ApoA-1 amyloid.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that apoA-I amyloid fibrils extracted from patients with hereditary apoA-I amyloidosis consist of the N-terminal 9 -11-kDa fragments; the fibrillar deposits in the heart contain mainly the 1-93 fragment, whereas those in other organs contain fragments ranging from approximately residues 1-80 to 1-100 (12,13). In the Iowa (G26R) mutation, the major protein constituent of the fibrils isolated from spleen and liver was found to be residues 1-83 of apoA-I (21).…”
Section: Discussionmentioning
confidence: 99%
“…So far, there are about 20 known mutations in the APOA1 gene associated with hereditary systemic apoA-I amyloidosis (9,10), among which G26R, the first and most common amyloidogenic mutation (11)(12)(13), is characterized by amyloid deposits in the peripheral nerves, kidneys, liver, and gastrointestinal tract (11,14). Although the precise mechanism for the amyloidogenicity of variant apoA-I remains unclear, it is thought that an unstable N-terminal helix bundle conformation associated with amyloidogenic mutations promotes proteolytic cleavage of the full-length protein (10,15,16), which deposits in the extracellular space of target tissues (17).…”
mentioning
confidence: 99%